Perinatal and infant autopsy. Issue 1 (4th April 2006) - Adappa, R; Paranjothy, S; Roberts, Z; Cartlidge, P H T
Abstract : Objectives: To measure perinatal and infant autopsy rate in Wales over a 10-year period and study factors influencing the decision to perform an autopsy. Design: Retrospective cohort analysis of data from the All Wales Perinatal Survey. Methods: Autopsy rates were calculated over a 10-year period (1994–2003), and reasons for not performing an autopsy were noted. Two time periods, 1994–1996 and 2001–2003 were compared, to study changing autopsy patterns. Results: Over the 10-year period, there were 4393 perinatal and infant deaths, with data available for 4306 (98%) cases. Consent for autopsy was requested in 89% of cases and granted in 68%. When compared, the 3-year cumulative autopsy rate fell from 67.5% (95% confidence interval (CI) 65% to 69%) in 1994–1996, to 52.7% (CI 49% to 55%) in 2001–2003. The difference in the proportion of autopsies performed between the two time periods was 14.8% (CI 11% to 18%). Parental consent was granted in 76.2% (CI 73% to 78%) of cases in 1994–1996 and 60% (CI 57% to 63%) of cases in 2001–2003. The difference in proportion in consent for autopsy in the two time periods was 16% (CI 12% to 20%). Conclusions: A decrease in perinatal and infant autopsy rates has been found in Wales over the past 10 years. Parental refusal has been the main cause of this decline.